ANALYSIS OF THE EFFECTIVENESS OF NATIONAL EARLY WARNING SCORE (NEWS) USAGE ON THE OUTCOMES OF HEAD INJURY - Laila Agustina; Abdurahman Wahid; Ifa Hafifah (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
NEWS (National Early Warning Score) is a new developmental instrument for early detection of declining patient conditions. Head injury is still a problem in Indonesia and so far its assessment is still based on GCS to know the category of head injury. Therefore, an appropriate early assessment instrument is needed to detect outcomes thus a management plan can be done quickly and accurately. This study aims to know the effectiveness of NEWS use against the outcome of head injury patients. The design of this study is a prospective cohort. Samples were taken by consecutive sampling in 48 head injured patients in three hospitals. The study was conducted from 27 November 2017 to 08 January 2018 with observation and documentation study. The result of analysis shows that p-value is 0,013 <0,05 (H0 is rejected), meaning that there is difference of outcome according to NEWS category. Significant differences were seen in mild and severe category of NEWS (0.013 <0.05). The percentage of NEWS influence on outcome is 78.34%. This suggests that NEWS is effectively used for initial assessment of outcomes of partients with head injury.